Integrasi Laboratorium Alam dan Laboratorium Buatan sebagai Inovasi Pembelajaran Bahasa Arab di Era Digital - M. Fiqih Dwi Firmansyah; Muhammad Noval Alviansyah; Muhammad Havis Ghozali; M. Yunus Abu Bakar (Kampus Akademik Publiser, 2026)
Students' prior knowledge is a crucial factor influencing the success of the learning process, as it relates to the knowledge, experience, and skills students possess before learning more complex material. Therefore, identifying prior knowledge through diagnostic assessment is a crucial step for teachers in understanding students' learning readiness, characteristics, and learning needs. Diagnostic assessment can be conducted through test and non-test techniques, such as pretests, written tests, interviews, observations, and questionnaires, to gain insight into students' prior understanding, background, and learning styles. The information obtained can then be used by teachers to determine appropriate learning strategies and objectives for the students. By accurately understanding students' prior knowledge, the learning process can be designed more effectively, enabling students to connect existing knowledge with new material being learned.